Correlative Assembly of Subsynaptic Nanoscale Organizations During Development - Sun, Shi-Yan; Li, Xiao-Wei; Cao, Ran; Zhao, Yang; Sheng, Nengyin; Tang, Ai-Hui (Frontiers in Synaptic Neuroscience, 2022)
Nanoscale organization of presynaptic proteins determines the sites of transmitter release, and its alignment with assemblies of postsynaptic receptors through nanocolumns is suggested to optimize the efficiency of synaptic transmission. However, it remains unknown how these nano-organizations are formed during development. In the present study, we used super-resolution STORM imaging technique to systematically analyze the evolvement of subsynaptic organization of three key synaptic proteins, RIM1/2, GluA1 and PSD-95 during synapse maturation in cultured hippocampal neurons. We found that volumes of synaptic clusters and their subsynaptic heterogeneity increase as synapses get matured. Synapse sizes of pre- and postsynaptic compartments correlated well at all stages, while only more mature synapses demonstrated a significant correlation between pre- and postsynaptic nano-organizations. After a long incubation with inhibitor of action potentials or AMPA receptors, both pre- and postsynaptic compartments showed increased synaptic cluster volume and subsynaptic heterogeneity, however, the trans-synaptic alignment were intact. Together, our results characterize the evolvement of subsynaptic protein architectures during development and demonstrate that the nanocolumn is organized more likely by an intrinsic mechanism and independent on synaptic activities.